FRI0406 Prevalence estimate and gender distribution of axial spondyloarthritis among patients in us rheumatology practices. (23rd January 2014) - Rao, S.A.; Shillington, A.C.; Strand, V.; McGuire, M.; Cifaldi, M.A.
Abstract : Background: The ASsessment in Ankylosing Spondylitis (ASAS) international Society working group has proposed and validated new classification criteria for patients with axial SpA. 1 Currently, there are no epidemiology data specific to axial SpA following the ASAS criteria. To our knowledge, this is the first study to estimate the prevalence of axial SpA using ASAS criteria. Objectives: To estimate the prevalence of axial SpA in a representative sample of rheumatology practices and apply it to US census data. Methods: 101 US rheumatology practices were selected in a stratified random fashion to assure geographic representativeness. Screening forms were used to identify at-risk patients aged 18 to 44 years with chronic low back pain, and medical records were randomly selected from this pool for review against ASAS axial SpA criteria. Overall prevalence was estimated by calculating the ratio of Axial SpA patients who met ASAS criteria and applying this ratio to the total number of at-risk patients treated at participating sites. Following post-stratification weighting to reflect geographic distribution, the average proportion of patients with axial SpA treated at selected sites was multiplied by the total number of US rheumatology practices to obtain an estimate of total at-risk patients treated by rheumatologists. Finally, US census data 2 were used to obtain a national prevalence estimate. Results: In a sample of 816 randomly selected records of at-risk patients, 553 (68%) were men, and 263 (32%) were women. 514 patients (63%) met ASAS criteria for prevalent axial SpA. Of these 389 (76%) were men, and 125 (24%) were women. By applying the prevalence estimates to the pool of 1, 217, 097 at-risk Americans, we estimated that 766, 771 at-risk patients treated by rheumatologists would meet ASAS criteria for axial SpA. This estimate corresponds to a national prevalence of 0.70% or 701 per 100, 000 individuals. Rheumatologists diagnosed axial SpA in 491 (60%) patients in the at-risk pool, regardless of whether or not they reported using ASAS criteria. The prevalence of axial SpA diagnosed by rheumatologists' assessment was 0.66%. Finally, the prevalence estimate of non-radiographic axial SpA based on ASAS criteria was 0.35%. Conclusions: This is the first systematic epidemiology study of axial SpA. The prevalence estimates according to ASAS criteria are 0.70% for axial SpA and 0.35% for non-radiographic axial SpA, with a proportionally higher prevalence in men than women. Overall, diagnosis of axial SpA in US rheumatology practices appears to be consistent with ASAS classification criteria. References: Rudwaleit M, et al. Ann Rheum Dis. 2009;68:770–83. http://www.census.gov/population/www/projections/projectionsagesex.html . Disclosure of Interest: S. Rao Shareholder of: Abbott, Employee of: Abbott, A. Shillington Employee of: EPI-Q, under contract with Abbott, V. Strand Consultant for: Abbott, M. McGuire Employee of: EPI-Q, under contract with Abbott, M. Cifaldi Shareholder of: Abbott, Employee of: Abbott